Mitigating Ergonomic Risks through Lean Ergonomics and Karakuri Kaizen Using NBM and RULA: A Case Study of Visual Inspection Operators in Automotive Manufacturing - Abdul Ajid; Adi Widya; Christa Pratiwi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research is aimed at the reduction of ergonomic risk factors and complaints of work-related musculoskeletal disorder (WMSDs) among visual inspection operators in the automotive component industry using the integration of Lean Ergonomics and Karakuri Kaizen. A case study was carried out at PT Kanemitsu SGS Indonesia focusing on five visual inspection operators. Ergonomic risk factors were analyzed using the Nordic Body Map (NBM) to evaluate musculoskeletal discomfort and the Rapid Upper Limb Assessment (RULA) for working postures. Primary assessments revealed the presence of significant ergonomic risk factors which resulted in the average NBM score of 62.6 and RULA score of 7 which indicates the presence of risk factors regarding working posture and action required correction on an urgent basis. Ergonomic modifications were accomplished by workstation redesigning based on the principles of anthropometry, which is the science of design and proportions of the human body, layout optimization, and integration of gravity-assisted Karakuri mechanisms to alleviate manual lifting and forward bending. The post-intervention assessment revealed the ergonomic risk factors have been significantly minimized and the NBM score and RULA score are now 28.8 and 3 respectively. Also, there was more than 75% reduction in the frequency of forward bending, which decreased from more than 80 occurrences per shift to less than 20. As such, the application of the two concepts in tandem suggests they may provide a viable and cost-effective solution to the balance of ergonomics and sustainable improvement to the comfort and productivity of the systems workers use in the automotive industry manual visual inspection systems.